2020
DOI: 10.3762/bjnano.11.44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physicochemical properties that modulate nanoparticle aggregation in blood

Abstract: Inorganic materials are receiving significant interest in medicine given their usefulness for therapeutic applications such as targeted drug delivery, active pharmaceutical carriers and medical imaging. However, poor knowledge of the side effects related to their use is an obstacle to clinical translation. For the development of molecular drugs, the concept of safe-by-design has become an efficient pharmaceutical strategy with the aim of reducing costs, which can also accelerate the translation into the market… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Although a decrease of ζ-potential was detected, as a consequence of the formation of a protein corona, no substantial agglomeration was observed, likely because of a stabilizing effect of adsorbed serum proteins by steric hindrance. This effect was similar to our previous observations in human plasma and blood [23]. Taken together, these results suggest that CNPs possess several desirable properties, including colloidal stability in relevant media.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although a decrease of ζ-potential was detected, as a consequence of the formation of a protein corona, no substantial agglomeration was observed, likely because of a stabilizing effect of adsorbed serum proteins by steric hindrance. This effect was similar to our previous observations in human plasma and blood [23]. Taken together, these results suggest that CNPs possess several desirable properties, including colloidal stability in relevant media.…”
Section: Discussionsupporting
confidence: 91%
“…These CNPs were shown to be noncytotoxic toward a murine macrophage cell line and significant antioxidant activity was observed, as a consequence of their ability to scavenge hydroxyl radicals. Finally, in a subsequent study CNPs were shown to remain stable in human plasma and blood, implying good hematocompatibility [23].…”
mentioning
confidence: 88%
“…However, at several levels there is high complexity associated with the hazard assessment of NBM, both for human risks as well as for the environment [ 21 , 22 ]. Common issues are dealing with the physicochemical identity of the NBMs, the existence of different nanoforms and their transformations in physiological and environmental media (e.g., biocorona formation, weathering/ageing) [ 23 , 24 , 25 ]. In addition, it can be questioned which are the most relevant biomarkers for NBM hazard testing and whether they are currently adequately addressed in the Organisation for Economic Co-operation and Development (OECD) guidelines used for regulatory purposes.…”
Section: The Biorima Risk Management Frameworkmentioning
confidence: 99%
“…The interference of nanomaterials with platelets and the resulting enhancement of platelet aggregation behavior may strongly hamper their use in therapeutic applications, blood analytics, and diagnostics [ 15 ]. The use of nanomaterials as carriers in the bloodstream requires that these materials minimally interfere with the clotting system.…”
Section: Introductionmentioning
confidence: 99%